Integration of Ayurvedic Knowledge in School Education: A Study from Varanasi - Hanspal, Gauri; Goswami, P K (International Research Journal of Ayurveda & Yoga, 2025)
Background: This study investigates the integration of Ayurvedic knowledge in school education by analyzing the National Council of Educational Research and Training (NCERT) textbooks (Classes 6–12) and assessing awareness among senior secondary students in Varanasi city. Objectives: The research aims to evaluate the representation of Ayurveda in NCERT textbooks and to measure students’ awareness and understanding of Ayurvedic concepts across different demographic variables such as gender and school type. Methodology: Employing a descriptive survey design, data were collected from 847 students across government and private schools. The NCERT textbooks were systematically reviewed for content related to health, hygiene, diet, yoga, and traditional medicine. Results: The findings revealed that while most students possessed a moderate level of awareness regarding Ayurveda, only a limited proportion demonstrated high knowledge. Female students and those from private schools exhibited significantly higher awareness levels. Chi-square analysis confirmed statistically significant associations between awareness, gender, and school type. Conclusion: The study highlights a notable gap between curricular representation and actual student awareness, underscoring the need for structured, experiential, and equitable integration of Ayurvedic concepts in school education. Recommendations: Curriculum enhancement, experiential learning initiatives, teacher capacity building, and alignment with the National Education Policy (NEP) 2020 are recommended. The findings provide meaningful insights for policymakers, educators, and curriculum developers to promote the effective inclusion of Indian Knowledge Systems in contemporary education.